Status and culture how our desire for social rank creates taste, identity, art, fashion, and constant change - Marx, William 1966- (Viking, 2022)
"An examination of how individuals strive for social status and how this creates our culture as a whole Contrary to belief, status signaling isn't just the province of the immature or insecure but a fundamental human need to secure social standing. It drives our behavior, forms our tastes, determines what we buy, and ultimately shapes who we are. It's what's behind "cool" and what drives fashion, music, food, sports, slang, travel, hairstyles, and dog breeds--and even the outsize influence of unpopular things with the "right" audience. In Status and Culture, W. David Marx weaves together history, psychology, sociology, anthropology, economics, philosophy, linguistics, semiotics, cultural theory, literary theory, art history, media studies, and neuroscience to reveal for the first time the inner workings of status. While there have been some explorations in the past of how status needs affect our individual behavior, Status and Culture seeks to go one step deeper and link the behavior of individuals to the formation of our broader culture. Marx examines three fundamental questions: Why do individuals cluster around arbitrary behaviors and take deep meaning from them? How do distinct styles, conventions, and sensibilities emerge? Why do we change behaviors over time and why do some behaviors stick around? Answering these long-standing mysteries then provides us with new perspectives for understanding the ephemeral and often baffling nature of internet culture. Status and Culture is a book that will appeal to business people, students, aspiring artists, and anyone who has ever wondered why things become popular or why they often feel pressured to go against their personal tastes. The reader will gain an understanding of the general rules that can be applied to everyday life and feel empowered by better appreciating the effect of social influence on their choices"--
Place of publication from publisher's website
Keywords: Sozialstatus; Identität; Sozialer Wandel; Kultur; Social status; Identity (Psychology); Culture; Social change; Statut social; Identité (Psychologie); social status